ORIGINS OF THE SAMATHUVAPURAM SCHEME: DR. M. KARUNANIDHI’S VISION FOR SOCIAL INTEGRATION AND EQUALITY IN TAMIL NADU (International Journal of Food and Nutritional Sciences, 2022)
The Samathuvapuram scheme, introduced by Dr. M. Karunanidhi during his tenure as Chief Minister of Tamil Nadu, represents a distinctive approach to addressing caste-based divisions through planned social integration. Initiated in 2006, the programme aimed to promote social equality by establishing residential settlements that bring together families from different castes, religions, and socio-economic backgrounds within a shared living environment. These settlements were developed with uniform housing and common access to essential facilities such as education, healthcare, and community spaces, thereby reinforcing the principles of equality and collective coexistence. By combining state-supported housing assistance with a model of mixed-community habitation, the scheme sought to reduce social segregation and encourage everyday interaction among diverse groups. While practical challenges and varying levels of success have influenced its implementation, Samathuvapuram remains a significant social reform initiative that reflects a broader commitment to social justice and inclusive development. The scheme continues to serve as an important reference point for policies aimed at fostering social cohesion and reducing structural inequalities in India.